Indonesia Health Financing System Assessment : Spend More, Spend Right, Spend Better - Pinto, Rebekah; Masaki, Emiko; Harimurti, Pandu (Washington, DC: World Bank, 2017)
This brief draws from the health financing system assessment (HFSA), which is a diagnostic assessment protocol aimed at identifying critical constraints and opportunities facing Indonesia’s health financing system. The overarching objective of the main HFSA report, as well as this policy brief is to inform the development of short-term and longer-term health financing strategies and reforms aimed at sustaining progress towards universal health coverage (UHC).